Ammonia–methane combustion in tangential swirl burners for gas turbine power generation. (1st January 2017) - Valera-Medina, Agustin; Marsh, Richard; Runyon, Jon; Pugh, Daniel; Beasley, Paul; Hughes, Timothy; Bowen, Phil
Highlights: Ammonia can become a new energy vector for large scale power generation. Ammonia fuelled gas turbines have been barely studied. Scarce literature exist. Current research provides findings that show NH3 potential as gas turbines fuel. Unfortunately, weak flame stability and high emissions are still restrictive. Stratified injection with low swirl might be the best way to use these blends. Abstract: Ammonia has been proposed as a potential energy storage medium in the transition towards a low-carbon economy. This paper details experimental results and numerical calculations obtained to progress towards optimisation of fuel injection and fluidic stabilisation in swirl burners with ammonia as the primary fuel. A generic tangential swirl burner has been employed to determine flame stability and emissions produced at different equivalence ratios using ammonia–methane blends. Experiments were performed under atmospheric and medium pressurised conditions using gas analysis and chemiluminescence to quantify emission concentrations and OH production zones respectively. Numerical calculations using GASEQ and CHEMKIN-PRO were performed to complement, compare with and extend experimental findings, hence improving understanding concerning the evolution of species when fuelling on ammonia blends. It is concluded that a fully premixed injection strategy is not appropriate for optimised ammonia combustion and that high flame instabilities can be produced at medium swirl numbers, hence necessitating lower swirl and a different injection strategy for optimised power generation utilising ammonia fuel blends.